A SYSTEMATIC LITERATURE REVIEW ON THE INFLUENCE OF SKILLS, DISCIPLINE, AND MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH REWARD AND PENALTY SCHEMES - Ramandhita Dwi Pranata; Budi Eko Soetjipto; Ludi Wisnu Wardhana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the relationship between skills, work discipline, and motivation on employee performance, with a reward–penalty scheme as a mediating variable. A Systematic Literature Review (SLR) based on the PRISMA 2020 protocol was conducted, analyzing 36 Scopus-indexed articles published in the last five years. The results show that technical, digital, and interpersonal skills, along with work discipline and motivation, significantly influence performance. Discipline represents strategic behavior, while motivation acts as a psychological catalyst. The reward–penalty scheme mediates the relationship between personal factors and productivity. The study highlights an integrative trend in human resource management. Identified gaps include the lack of a comprehensive conceptual model, limited longitudinal studies, and minimal exploration of non-financial rewards and organizational culture. These findings reinforce Self-Determination Theory, Resource-Based View, and Behavioral Reinforcement Theory, while offering practical insights for developing competency systems, value-based discipline, and adaptive incentives.